The faculty’s perceptions on the importance of English oral proficiency and communication problems faced by ESL medical students. - Abdul Malik, Faridah; Othman, Khairiah (2018)
As part of a professional healthcare team, doctors value communication as a means to unite the team around the common goal of treating patients. As the lingua franca of 21st century Medicine, the mastery of English is an essential component of communication. English is required for communication between peers and colleagues, to present symptoms and come up with differential diagnoses, to plan a course of medical intervention, to refer cases and patients to specialist centres and myriad other uses all requiring extensive use and mastery of English especially in terms of oral skills. Therefore, it is essential that we identify any weaknesses in our medical graduates at an early stage and rectify those weaknesses so as to produce competent and communicative medical graduates in the future. This paper reports on the findings of a survey on the medical lecturers’ perceptions on the importance of English oral skills for success in medical study and future career of their ESL medical students as well as the problems that their students might face pertaining to their English oral ability. The findings of the study can provide insights into developing English language programmes that better meet the needs of these students.